Recent Advances in Design Strategies and Multifunctionality of Flexible Electromagnetic Interference Shielding Materials - Cheng, Junye; Li, Chuanbing; Xiong, Yingfei; Zhang, Huibin; Raza, Hassan; Ullah, Sana; Wu, Jinyi; Zheng, Guangping; Cao, Qi; Zhang, Deqing; Zheng, Qingbin; Che, Renchao (Nano-micro letters, 2022)
Highlights Detailed summary of current trends in the advancement of flexible EMI shielding materials. The theoretical shielding mechanisms and the latest concept of "green shielding" index (g s ) are outlined. Functional applications of flexible EMI shielding materials are introduced from thermal conductivity, hydrophobicity to transparency, sensing even multiple functions. Exclusive insights in challenges and future design strategies opportunities for flexible EMI shielding materials are provided. With rapid development of 5G communication technologies, electromagnetic interference (EMI) shielding for electronic devices has become an urgent demand in recent years, where the development of corresponding EMI shielding materials against detrimental electromagnetic radiation plays an essential role. Meanwhile, the EMI shielding materials with high flexibility and functional integrity are highly demanded for emerging shielding applications. Hitherto, a variety of flexible EMI shielding materials with lightweight and multifunctionalities have been developed. In this review, we not only introduce the recent development of flexible EMI shielding materials, but also elaborate the EMI shielding mechanisms and the index for "green EMI shielding" performance. In addition, the construction strategies for sophisticated multifunctionalities of flexible shielding materials are summarized. Finally, we propose several possible research directions for flexible EMI shielding materials in near future, which could be inspirational to the fast-growing next-generation flexible electronic devices with reliable and multipurpose protections as offered by EMI shielding materials.